Straw Bank Community Intervention in the Glagahweroh Village Farmer Group, Kalisat District, Jember Regency - Rhoma Dion Rahardiansyah; Anggita Rizky Suci Irawan; Refina Imaniar Esa; Mury Ririanty; Novia Luthviatin; Taufan Asrisyah Ode (ABDIMAYUDA: Indonesia Journal of Community Empowerment for Health, 2023)
Jember Regency is a district that has tremendous potential in agriculture with a land area of 2,431 Km² and geographically located at position 6°27'9°-7°14'33° East and 7° 59'6° - 8°33'56 ° LS. This can be an opportunity for Jember Regency to have the potential for export commodities in the agricultural sector. The rice harvest area in 2021 is around 124,027.77 hectares. Agricultural waste such as straw which is usually burned can cause increased carbon emissions and air pollution which are harmful to health and increased greenhouse gas emissions which can cause an increase in the average temperature on earth. One effort that can be made to deal with straw burning is community intervention. Community intervention activities were carried out at the Farmer Group's house with socialization on the use of rice straw residue as organic fertilizer. This activity aims to add insight and knowledge to the people of Glagahwero Village regarding straw burning and can reduce straw burning which causes various impacts by using turning straw into organic compost. Socialization activities on the use of straw were carried out by displaying power points, distributing leaflets containing the impact, and how to make compost and also showing a video. The results of the study showed that there was an increase in knowledge by providing a question and answer session after giving the material and the number of audience present was 33 people, indicating that the level of attendance has exceeded the target we set.